A successful school improvement intervention at the micro level: is this enough to achieve sustainable changes in the argentine education system? - María Eugenia G. T. de Podestá; María Victoria Abregú; Marcela Zinn (Universidad Autónoma de Madrid, 2015)
For decades the Argentine education system was structured as a centralised pyramid, where decisions were made vertically with great prescription and control. In 1960, signs began to surface indicating that this educational structure did not adapt to new pedagogical trends or to the changing economic conditions of the country (Gvirtz, 2004).